COMMUNITY EMPOWERMENT AND CUSTOMARY ATTACHMENTS SUPPORT PARTICIPATION IN AAN TOURISM VILLAGE DEVELOPMENT - Farel, Filipus; Sutiarso, Moh Agus; Tunjungsari, Komang Ratih (LPPM Universitas Jambi, 2023)
This study aims to determine the tourism potential in Aan Tourism Village and community participation in the development of Aan Tourism Village. The research carried out with descriptive qualitative methods is expected to increase insight and knowledge about community involvement, especially in developing tourism villages. Aan Village has a variety of interesting tourism potentials in the form of views of hills, rice fields, waterfalls, and unspoiled rivers. In addition to nature-based tourist attractions, the people of Aan village have diverse and unique cultures and arts. Community involvement in developing Aan tourism village as a whole is quite optimal, which is more dominated by community members with backgrounds and tourism experience. Community involvement in tangible forms of energy includes participation in mutual aid activities, being a tour guide, and providing culinary. While in the form of property, among others, in the form of providing honey bee cultivation assets, facilities, and exhibition places for craft art and painting. The driving factors for community participation in the development of Aan tourism village, which include willingness, ability, and opportunity, are good.